2019
DOI: 10.1016/j.jhep.2019.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of abdominal MRI data identify genes regulating hepcidin as major determinants of liver iron concentration

Abstract: Genome-Wide Association Study (GWAS) Higher Blood pressure Arthritides Neuropsychiatric conditions Malignancies Lower Anaemias Lipidaemias Ischaemic heart disease Genetically higher central obesity Highlights Variants in HFE and TMPRSS6 are associated with higher liver iron. There is genetic evidence that higher central obesity causes higher liver iron. Liver iron variants are not organ specific and associate with multiple diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 53 publications
6
35
0
Order By: Relevance
“…The novelty of the study by Chen et al extended to the evaluation of the impact of risk variants on non liver‐related traits. In line with independent findings, both the HFE and SERPINA1 variants decreased circulating lipids, thereby possibly contributing to fatty liver by inducing endoplasmic reticulum stress and impairment of lipoprotein secretion …”
Section: Common Genetic Causes Of Cirrhosis In Europeanssupporting
confidence: 89%
See 3 more Smart Citations
“…The novelty of the study by Chen et al extended to the evaluation of the impact of risk variants on non liver‐related traits. In line with independent findings, both the HFE and SERPINA1 variants decreased circulating lipids, thereby possibly contributing to fatty liver by inducing endoplasmic reticulum stress and impairment of lipoprotein secretion …”
Section: Common Genetic Causes Of Cirrhosis In Europeanssupporting
confidence: 89%
“…However, this interpretation is consistent with new evidence indicating that heterozygous carriage of HFE p.C282Y and SERPINA1 p.E342K variants, previously deemed as autosomal recessive traits, favours liver disease . In addition, hepatic fat has recently emerged as a major determinant of iron stores by facilitating iron absorption, especially in carriers of HFE p.C282Y and SERPINA1 p.E342K . Chen et al also highlighted that HFE p.C282Y favours haemoglobinization, thereby protecting against iron deficiency and anaemia, which might have provided an evolutionary advantage to carriers .…”
Section: Common Genetic Causes Of Cirrhosis In Europeanssupporting
confidence: 71%
See 2 more Smart Citations
“…Genetic testing is required to differentiate true genetic hemochromatosis (homozygous C282Y) from the other forms of milder hemochromatosis or even secondary iron overload syndromes [22,119]. Recent studies have identified elevated iron without homozygosity for the p.C282Y variant in the HFE gene, highlighting the continued undetected disease existing in the general population [120][121][122]. Increased iron can be co-existing in NAFLD, ALD and other chronic liver diseases [22,122,123].…”
Section: Applications Of Mpmri In Chronic Liver Disease Haemochromatosismentioning
confidence: 99%